Tataniaga Komoditas Padi (Oryza Sativa L.) Di Kecamatan Papar Kabupaten Kediri - Amirroh Khoirunnisa, Siti; Winahyu, Nastiti; Puji Astoko, Endro (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2025)
The aim of this research is to determine marketing channels and analyze farmer's share of rice commodities in Papar District. This research uses analysis of costs, margins, farmer's share, and the ratio of profit per trading cost. The research results show that the dynamics of rice trading in Papar District involve several institutions that have an important role in creating an efficient supply chain. Farmers as primary producers interact with various institutions, such as farmers, middlemen, collectors, and retail agents, who are interconnected to meet consumer needs. The dominance of the use of certain marketing channels reflects the adaptation of business actors to fluctuating market demand. Farmers get the largest share if they can cut marketing channels. These findings raise interesting questions about how changes in supply chains can impact farmers' sustainability and welfare, as well as what strategies need to be adopted to optimize profits without compromising rice accessibility for consumers. Recognizing the importance of relationships between all institutions in the trading system, this research opens up space for deeper discussions about the agribusiness system and the challenges that exist at the local level.